College transition: managing stress and maintaining health focus group report - Janke, James; Speerstra, Mandy; Trechter, David (My University, 2006)
The Survey Research Center conducted a series of focus group sessions at the request of a team of University of Wisconsin-Extension faculty from the Western and Northern Districts. The purpose of the focus groups was to be a source of input for a research project designed to develop a curriculum to help students and their families make the transition from high school to college.
42 p.
Keywords: Transition to college; Student adjustment--Wisconsin; High school students--Wisconsin; College student orientation--Wisconsin; College students--Wisconsin